2021
DOI: 10.1039/d0nr07858a
|View full text |Cite
|
Sign up to set email alerts
|

Tailored growth of graphene oxide liquid crystals with controlled polymer crystallization in GO-polymer composites

Abstract: Kinetics of polymer crystallization determines the liquid crystallinity of graphene oxide and its long range alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…This work demonstrates another possible application of crystallization for ordering LCs. 135 To the best of our knowledge, no study has been published in the literature that reports on the ordering of CNC LCs employing polymer crystallization. Similar ordering through application of an electric field has been observed in clay suspensions; 136 similarly anomalous photothermal deformation of gels doped with uniaxially aligned nanosheets adsorbed with a dye is observed in one study.…”
Section: Liquid Crystal Formation Of Cncsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work demonstrates another possible application of crystallization for ordering LCs. 135 To the best of our knowledge, no study has been published in the literature that reports on the ordering of CNC LCs employing polymer crystallization. Similar ordering through application of an electric field has been observed in clay suspensions; 136 similarly anomalous photothermal deformation of gels doped with uniaxially aligned nanosheets adsorbed with a dye is observed in one study.…”
Section: Liquid Crystal Formation Of Cncsmentioning
confidence: 99%
“…The cholesteric layer self-assembled from the droplet’s bottom center and diffused to the hydrophilic glass substrates’ edges. 212 As a result of the edge-center ordered drying technique, 135 the iridescent coating films formed on PS, SS, glass, Cu–Zn alloy, and Cu–Ni alloy display characteristic “coffee rings”. The conclusions of this study apply to spray coating on a variety of substrates; research reports on whether iridescent color spontaneously appears on examined surfaces.…”
Section: Applicationsmentioning
confidence: 99%
“…However, aligning GO nanostructures inside the polymer matrix could potentially improve the performance further. Few works have focused on this topic [73][74][75][76][77]. For example, Cheng et al [74] showed that aligning 2D GO nanosheets inside the PEO polymer results in higher room temperature ionic conductivity.…”
Section: Dimensional and Aligned Go As Fillers In Spesmentioning
confidence: 99%
“…In such a structure, the ion transport is guided by GO nanoplatelets and the oriented PEO lamellae, leading to high anisotropic ionic conductivity. Another study also focused on controlling the filler direction in GO-polymer composite electrolytes [75]. While it is known that GO nucleates polymer crystallization, polymer crystallization also has an impact on the microstructure of GO.…”
Section: Dimensional and Aligned Go As Fillers In Spesmentioning
confidence: 99%
“…The incorporation with polymer additives has been confirmed as an effective way for the improvement of GO LCs' stability, 35 and GO alignment in composites. 36 Polyvinyl alcohol (PVA) is an inexpensive, biofriendly and stable polymer, which is compatible with GO sheets at molecular level, 37 and can crosslink with GO sheets by chemical conjugation, 38 thereby enhancing the mechanical strength and structural stability of the GO/PVA nanocomposite. As reported by Li et al, PVA-intercalated GO membranes were facilely achieved, which could toughly withstand ultrasonication destruction and showed stable and reliable desalination performance.…”
Section: Introductionmentioning
confidence: 99%